Validation of the Smoking Cessation Counseling Scale Chinese Version in Taiwan. Issue 6 (November 2019) - Tsai, Hsiu-Wen; Chen, Shu-Ching; Wu, Hsein-Lin; Hong, Ming-Ying; Lee, Yun-Hsiang; Lai, Yeur-Hur
Abstract : Background: Providing tobacco control (TC) and smoking cessation (SC) counseling is an important part of healthcare. An assessment tool to understand healthcare providers' experiences in providing SC counseling may enhance TC. Objective: The aims of this study were to (1) translate and develop the Smoking Cessation Counseling Scale–Chinese version (SCCS-C) and (2) evaluate its psychometric properties in Taiwan. Methods: This is a 2-phase instrument testing study. In the first phase, the SCCS-C was developed and translated. In the second phase, 2 groups of participants were recruited. First, 292 SC educator trainees completed the psychometric assessment measures (internal consistency reliability and construct validity). The 2-week test-retest reliability was assessed in certified TC instructors. Results: The results showed that (1) the SCCS-C has satisfactory content validity and internal consistency reliability with a Cronbach's α of .96; (2) the overall 2-week test-retest reliability was 0.70; (3) instead of the 4-factor structure of the original scale, a 3-factor structure of the SCCS-C was identified by exploratory factor analysis to explain 65.37%; (4) construct validity was supported by significant negative correlations between SCCS-C and barriers regarding TC and positive correlations with counseling, responsibility, and self-efficacy; and (5) discriminant validity was supported by significant differences between SC educator trainees and the certified TC instructors, as well as between those living with or without smokers. Conclusions: The SCCS-C has satisfactory reliability, test-retest reliability, and construct validity. Implications for Practice: The SCCS-C is a valid, reliable instrument for assessing healthcare counseling activities for SC in Taiwan.